Bacillus Calmette–Guérin Treatment Changes the Tumor Microenvironment of Non-Muscle-Invasive Bladder Cancer - Su, Fei; Liu, Ming; Zhang, Wei; Tang, Min; Zhang, Jinsong; Li, Hexin; Zou, Lihui; Zhang, Rui; Liu, Yudong; Li, Lin; Ma, Jie; Zhang, Yaqun; et al. (Frontiers in Oncology, 2022)
Background Bacillus Calmette–Guérin (BCG) is currently the most effective intravesical therapy for non-muscle-invasive bladder cancer (NMIBC) as it can prevent disease recurrence and progression and lower mortality. However, the response rates to BCG vary widely and are dependent on a multitude of factors. Methods We performed a systematic discovery by analyzing the whole exome sequence, expression profile, and immune repertoire sequence of treatment-naive and 5-year time-serial relapsed tumors from 24 NMIBC patients. Results BCG therapy showed bidirectional effects on tumor evolution and immune checkpoint landscape, along with a significant reduction of the percentage of neoantigen burden. In addition, a remarkable proportion of subclonal mutations were unique to the matched pre- or post-treatment tumors, suggesting the presence of BCG-induced and/or spatial heterogeneity. In the relapsed tumors, we identified and validated a shift in the mutational signatures in which mutations associated with aristolochic acid (AA) exposure were enriched, implying AA may be associated with tumor recurrence. Enhanced expressions of immune checkpoint regulation genes were found in the relapsed tumors, suggesting that the combination of immune checkpoint with BCG treatment may be an effective strategy to treat NMIBC. TCR sequencing revealed treatment-associated changes in the T-cell repertoire in the primary and relapsed tumors. Conclusion Our results provide insight into the genomic and immune dynamics of tumor evolution with BCG treatment, suggest new mechanisms of BCG resistance, and inform the development of clinically relevant biomarkers and trials of potential immune checkpoint inhibitor combination therapies.